The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/f10080633
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Forest Structure and Composition along the Altitudinal Gradient in the State of Sikkim, Eastern Himalayas, India

Abstract: Understanding the structure and composition of native forests is a prerequisite in developing an adaptive forest management plan for Himalayan forest ecosystems where climate change is rapid. However, basic information on forest structure and composition are still limited in many places of the Eastern Himalayas. In this study, we aimed to understand the diversity, structure, and composition of forests and their variations along an altitudinal gradient in Himalayan forests. The study was conducted in the Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…Furthermore, the inverse J-shaped pattern documented for overall size class distribution in this study is similar to the findings of Bhutia et al [32] who found the highest number of individuals in the smallest DBH class of 3 to 13 cm and least in the highest class in Eastern Himalayan, India. This pattern is further supported by the findings of Shrestha et al [139], Dar et al [140], Pandey et al [127], and Schwab [141].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the inverse J-shaped pattern documented for overall size class distribution in this study is similar to the findings of Bhutia et al [32] who found the highest number of individuals in the smallest DBH class of 3 to 13 cm and least in the highest class in Eastern Himalayan, India. This pattern is further supported by the findings of Shrestha et al [139], Dar et al [140], Pandey et al [127], and Schwab [141].…”
Section: Discussionsupporting
confidence: 91%
“…In lower-elevation tropical forests, higher species diversity and richness were recorded in high precipitation regions than dry regions in Myanmar by Khaine et al [123], and in mangrove forest [124] and sub-Saharan Africa [125] as well. Regarding forest structure, most studies [1,32,[126][127][128] have focused on Himalayan vegetation patterns along altitudinal gradients, though few have mentioned the importance of climate variables in predicting forest stand structure [21,129,130]. Considering forest structure varies with water availability [131], and environmental and biological factors control forest structure at higher elevations [132,133], this study tried to assess differences in forest structure along a precipitation gradient in the Annapurna range.…”
Section: Discussionmentioning
confidence: 99%
“…The forest stand represents the East Himalayan broad-leaved wet montane forests (Sudhakar et al 2008, Kanade andJohn 2018) characterized by (a) the dominance of broad-leaved evergreen species and (b) sub-tropical montane climate with high precipitation and strong diurnal and seasonal temperature gradients. The vegetation data were derived from five 0.1 ha (100 m X 10 m) vegetation survey plots laid in FWS as part of another study (Bhutia et al 2019). In each plot, all individuals above 30 cm circumference at breast height were enumerated and voucher samples were collected for identification.…”
Section: Confidential Manuscript Submitted To Treesmentioning
confidence: 99%
“…Forests have traditionally been exploited in the study sites in multiple ways to maximize economic and social benefits. Recently, the socioeconomic organization in the highaltitude areas and public attitudes towards the forest and forestry have changed dramatically with the growth of tourism and other recreational activities (Nepal 2002;Stevens 2003;Sacareau 2009;Neupane et al 2014;Mu et al 2019), and the goals of forest management now extend far beyond those of the past to embrace the demand for new ecological and recreational functions (Maren and Sharma 2018;Bhutiya et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the structure and composition of native forests is a prerequisite in developing an adaptive forest management plan for Himalayan forest ecosystems where climate change is rapid (Bhutiya et al 2019). Population demography is crucial to understand current species distribution patterns (Gaston 2009;Purves 2009;Bell et al 2013) and to predict their future dynamics (Pagel and Schurr 2012;Normand et al 2014).…”
Section: Introductionmentioning
confidence: 99%